2015
DOI: 10.2166/wst.2015.129
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of LID practices for restoring pre-development runoff regime in an urbanized catchment in southern Finland

Abstract: This study quantifies the effects of common stormwater management techniques on urban runoff generation. Simulated flow rates for different low impact development (LID) scenarios were compared with observed flow rates during different urban construction phases in a catchment (12.3 ha) that was developed from natural forest to residential area over a monitoring period of five years. The Stormwater Management Model (SWMM) was calibrated and validated against the observed flow rates in the fully developed catchme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 55 publications
(29 citation statements)
references
References 15 publications
4
25
0
Order By: Relevance
“…Ahiablame and Shakya reported that LID measures can be used to attenuate flood risks in an urban watershed . Guan et al reported that LID measures appeared to be effective in controlling flow quantity and water quality of runoff and mitigating the negative impacts of rapid urbanization …”
Section: Resultsmentioning
confidence: 99%
“…Ahiablame and Shakya reported that LID measures can be used to attenuate flood risks in an urban watershed . Guan et al reported that LID measures appeared to be effective in controlling flow quantity and water quality of runoff and mitigating the negative impacts of rapid urbanization …”
Section: Resultsmentioning
confidence: 99%
“…Guan et al . [] reported total runoff volume reduction in the range of 24.5%–78.3% for various hypothetical low impact development practices placed on an urban catchment. Walsh et al .…”
Section: Discussionmentioning
confidence: 99%
“…Green infrastructure is designed to mitigate storm water impacts, and its success at doing so has been reported in multiple studies [e.g., Roseen et al ., ; Damodaram and Zechman , ; Askarizadeh et al ., ; Guan et al ., ; Winston et al ., ]. Although the effectiveness of storm water management practices has been assessed for different climates and designs, there is a limited knowledge base for how these solutions impact, separately or jointly, catchment‐scale hydrology [ Bell et al ., ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The EPA SWMM was selected to perform the hydrological analysis in the studied urban catchment. SWMM is a widely used urban hydrological model for single event or long-term (continuous) simulation of runoff quantity and quality from primarily urban areas (Denault et al, 2006;Jang et al, 2007;Meierdiercks et al, 2010;Krebs et al, 2014;Guan et al, 2015a;Guan et al, 2015b). SWMM describes the urban catchment as a drainage network and a set of subcatchments connected to the network.…”
Section: Model Implementationmentioning
confidence: 99%